Phosphate solubilization and the enhancement of chickpea growth by new rhizospheric microorganisms Bacillus tequilensis and Trichoderma orientale - Bekkar, Ahmed Amine; Zaim, Souad (Archives of Biological Sciences, 2023)
Paper description: Microbial solubilization of phosphate to maintain soil fertility is an eco-friendly and less expensive alternative to chemical fertilizers. Species of soil Bacillus and Trichoderma that colonize mainly in the rhizosphere can solubilize soil-insoluble phosphates. Phosphate-solubilizing microorganisms (PSMs) were assessed in vitro and in vivo. The application of the two strains separately and in combination had a beneficial effect on germination by promoting the development of the seeds and effectively enhancing plant growth. This is the first report on the P-solubilizing potential of the combined microorganisms Bacillus tequilensis and Trichoderma orientale and their capacity to promote plant growth in chickpeas Abstract: Two Trichoderma strains and three Bacillus strains isolated from the rhizosphere of healthy chickpeas in Algeria were assessed for their phosphate solubilizing capacity in vitro as well as their growth effects on seedlings of the chickpea in pot experiments. The microorganisms tested had higher phosphate-solubilizing activities, with the solubilization index ranging from 2.41 to 7.40. The concentration of solubilized phosphate varied from 30.17 to 157.44 μg/mL. The maximum phosphate-solubilizing activity was observed in the two culture filtrates of Bacillus tequilensis Bt1 (157.44 μg/mL) and Trichoderma orientale T1 (143.33 μg/mL), accompanied by a decrease in pH of the growth medium from 4.51 to 5.75. The application of the strains (B. tequilensis Bt1 and T. orientale T1) separately and in combination had a beneficial effect on germination by promoting the development of the seeds and effectively enhancing plant growth. Chickpea seedlings showed better vegetative growth when treated with a mixture of B. tequilensis Bt1 and T. orientale T1 together than an individual treatment. To our knowledge, this is the first report of the phosphate-solubilizing potential of the combined microorganisms B. tequilensis and T. orientale and their capacity to promote plant growth in chickpeas.